Spatial regulation of the KH domain RNA‐binding protein Rnc1 mediated by a Crm1‐independent nuclear export system in Schizosaccharomyces pombe. Issue 3 (24th February 2017) - Satoh, Ryosuke; Matsumura, Yasuhiro; Tanaka, Akitomo; Takada, Makoto; Ito, Yuna; Hagihara, Kanako; Inari, Masahiro; Kita, Ayako; Fukao, Akira; Fujiwara, Toshinobu; Hirai, Shinya; Tani, Tokio; et al.
Summary: RNA‐binding proteins (RBPs) play important roles in the posttranscriptional regulation of gene expression, including mRNA stability, transport and translation. Fission yeast rnc1 + encodes a K Homology (KH)‐type RBP, which binds and stabilizes the Pmp1 MAPK phosphatase mRNA thereby suppressing the Cl − hypersensitivity of calcineurin deletion and MAPK signaling mutants. Here, we analyzed the spatial regulation of Rnc1 and discovered a putative nuclear export signal (NES)Rnc1, which dictates the cytoplasmic localization of Rnc1 in a Crm1‐independent manner. Notably, mutations in the NESRnc1 altered nucleocytoplasmic distribution of Rnc1 and abolished its function to suppress calcineurin deletion, although the Rnc1 NES mutant maintains the ability to bind Pmp1 mRNA. Intriguingly, the Rnc1 NES mutant destabilized Pmp1 mRNA, suggesting the functional importance of the Rnc1 cytoplasmic localization. Mutation in Rae1, but not Mex67 deletion or overproduction, induced Rnc1 accumulation in the nucleus, suggesting that Rnc1 is exported from the nucleus to the cytoplasm via the mRNA export pathway involving Rae1. Importantly, mutations in the Rnc1 KH‐domains abolished the mRNA‐binding ability and induced nuclear localization, suggesting that Rnc1 may be exported from the nucleus together with its target mRNAs. Collectively, the functional Rae1‐dependent mRNA export system may influence the cytoplasmic localization and function of Rnc1. Abstract : Pmk1 MAPK phosphorylates Rnc1, which binds and stabilize the MAPK phosphatase Pmp1 mRNA in the cytoplasm. The Rnc1/mRNA complex may be exported via the Rae1‐mediated mRNA export pathway. In the Rnc1 NES mutant, accumulation of Rnc1 in the nucleus leads to destabilization of Pmp1 mRNA. In the Rnc1 KH domain mutant, failure to bind to its target mRNAs induced its accumulation in the nucleus, presumably due to loss of nuclear export as an RBP/mRNA complex.